PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN FISIKA BERBASIS KOMPUTASI PADA GURU-GURU FISIKA SMA Se-ABEPURA - Noper Tulak; Yusuf Bungkang (JURNAL PENGABDIAN PAPUA, 2021)
Training on developing physics learning media for high school physics teachers in Abepura and surrounding areas was carried out on 15 and 16 August 2019 at computer laboratory of physics department. The aim of the training is to motivate and improve the ability of teachers to create virtual learning media as alternative physic learning media so as to improve the quality of teaching and physics learning.  The method used to support the success of this program is in the form of training, demonstration and practice or tutorial using matlab program. The results of the implementation of service activities felt by the team and the training participants were very satisfying, with indicators of participant activity in each activity process, and participating in training enthusiastically. The training of create  physics learning media for senior high school teachers in the community service program that has been implemented is expected to provide understanding and also the ability of teachers to design physics learning media using computers that will have an impact on increasing teaching and learning productivity and professionalism of physics teachers in senior high school. Keywords: learning media, Matlab, physic teachers